PREVENTION AS A SOCIAL DEFENSE MECHANISM - Nijaradze , G. (Modern Psychology, 2019)
Several behavioral patterns aiming to prevent social status/loosing face in various social situations are discussed. Some patterns (e.g. normative conformity, self-irony) are viewed as an individual’s trials to reduce the potential dissonance that may arise among the attendees towards him/her as a result of his/her social status incompatible behavior.
Keywords: prevention; defense mechanism; dissonance reduction; impression management